2016
DOI: 10.1002/ardp.201600236
|View full text |Cite
|
Sign up to set email alerts
|

From Lead to Drug Utilizing a Mannich Reaction: The Topotecan Story

Abstract: Natural products are a rich source of bioactive compounds, and numerous natural compounds have found application in cancer chemotherapy. However, unfavorable physicochemical properties often prevent the use of the original natural product as a drug. A prominent example is camptothecin from the Chinese tree Camptotheca acuminata, which shows extraordinary cytotoxic activity based on a specific molecular mode of action (inhibition of human topoisomerase I). Due to its extremely poor solubility, the original natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Topotecan (TPT) is a derivative of camptothecin which originates from the Camptotheca acuminata (108) and is used in the second-line treatment of ovarian cancer. A clinical trial demonstrated that TPT can downregulate HIF-1a in solid advanced tumours (109).…”
Section: Molecules Suppressed Ovarian Cancer Progression By Directly or Indirectly Downregulating Hif-1amentioning
confidence: 99%
“…Topotecan (TPT) is a derivative of camptothecin which originates from the Camptotheca acuminata (108) and is used in the second-line treatment of ovarian cancer. A clinical trial demonstrated that TPT can downregulate HIF-1a in solid advanced tumours (109).…”
Section: Molecules Suppressed Ovarian Cancer Progression By Directly or Indirectly Downregulating Hif-1amentioning
confidence: 99%
“…This stabilizes TOP1cc and prevents further religation of the broken DNA. When replication and transcription machineries encounter the trapped TOP1cc, DNA damage is generated, triggering cell death. , To date, four well-known camptothecin TOP1 inhibitors (Figure 2S, Supporting Information) have been approved for clinical treatment of cancers, including irinotecan ( 2 ) and topotecan ( 3 ), approved by the FDA, 10-hydroxycamptothecin ( 4 , HCPT, in China), and belotecan ( 5 , in South Korea). ,, Therefore, TOP1 is a validated target for the discovery of antitumor agents. , …”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with our previous methods, we have thus far developed tools to functionalize this highly complex natural product at C5, C6 and C8 with precision demonstrating the unique power of site selective C–H activation 22 , 29 . Notably, the structural modifications at these positions through semi-synthesis had led to the discovery of drugs, such as topotecan and irinotecan 30 .…”
Section: Resultsmentioning
confidence: 99%